Emotional Intelligence and Customer Orientation: Unveiling the Power of Salespeople in Nepalese Hospitality Industry (Nepalese Journal of Hospitality and Tourism Management, 2025)
This study examines the relationship between emotional intelligence (EI) and customer orientation (CO) among sales professionals in Nepal’s hospitality and service sectors. Recognising the increasing relevance of emotional skills in customer-facing roles, the research aimed to quantify how EI influences customer-oriented behaviours. Data were collected from 120 sales professionals through a structured online questionnaire using two validated scales: the Wong and Law Emotional Intelligence Scale (WLEIS)and the positively framed items of the Sales Orientation–Customer Orientation (SOCO)Scale. Structural Equation Modelling (SEM) confirmed a strong, statistically significant relationship between EI and CO (β ≈ 0.74, p < 0.001), explaining 54.5% of the variance. The model fit indicators confirmed the robustness and validity of the measurement tools. The findings highlight the importance of incorporating emotional intelligence into recruitment, training, and professional development initiatives to enhance customer satisfaction and service quality. Future research may benefit from examining additional mediating variables and broader organisational settings to build a more comprehensive framework.